Max Weber : - Bendix, Reinhard (University of California press, 1977)
The purpose of this book is to make Weber's sociological work more accessible and more thematically coherent than it is either in the original or in translation. This volume is used as an introduction to the study of orignal Weber texts and gives the reader a systematic presentation of Weber's sociological studies.